Drosophila insulin receptor regulates diabetes-induced mechanical nociceptive hypersensitivity. - Dabbara, H.; Schultz, A.; Im, S.H. (microPublication Biology, 2021)
Painful diabetic neuropathy (PDN) is one of the predominant complications of diabetes that causes numbness, tingling, and extreme pain sensitivity. Understanding the mechanisms of PDN pathogenesis is important for patient treatments. Here we report Drosophila models of diabetes-induced mechanical nociceptive hypersensitivity. Type 2 diabetes-like conditions and loss of insulin receptor function in multidendritic sensory neurons lead to mechanical nociceptive hypersensitivity. Furthermore, we also found that restoring insulin signaling in multidendritic sensory neurons can block diabetes-induced mechanical nociceptive hypersensitivity. Our work highlights the critical role of insulin signaling in nociceptive sensory neurons in the regulation of diabetes-induced nociceptive hypersensitivities.